What is the best way to deliver e-grocery orders in the UK? - Zhang, Lina (2015)
With the proliferation of e-commerce, e-grocery businesses are enjoying ever-increasing popularity around the world. Britain is regarded as the most developed e-grocery market and retailers in the UK are leading the way regarding e-fulfilment innovations. However, the uptake of e-grocery is not without its problem. The razor-thin margins of grocery retailing and high e-fulfilment costs have led to the bankruptcy or acquisition of many companies. It is common practice for e-grocery players to keep adjusting their e-fulfilment strategies and delivery related policies as there is no proven successful business model for e-grocers so far.